Approach to Personal Behaviour Finance - Bikas, Bikas; Jureviciene, Daiva (Publishing House of the Wrocław University of Economics, 2009)
This article analyses the dynamic of households’ savings ratio and impact of individual behaviour on savings and investment decisions making. The life cycle hypothesis and behaviour economics arc still a considerable theoretical instrument and they help the economists to take into consideration such important factors as wealth and expectations of future income while making households' consumption decisions. The considerable influence on savings' factors have economic, social, political and demographical processes of the state and in particular political and economic stability. Salary, price level, inflation, and GDP directly influence the saving process. Low household saving ratio in Lithuania indicates not only a high level of poverty, but also disproportional development of economy, misbalanced financial flows and household income to be slowly increasing. Lithuanian households' saving ratio shows that private sector do not lay aside funds for a retirement period. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 75-88